EFEKTIVITAS PEMBERIAN PREBIOTIK TERHADAP DURASI DIARE PADA ANAK PRA SEKOLAH DI RUANG DURIAN RUMAH SAKIT UMUM DAERAH KLUNGKUNG - Nara Kusuma, A.A. Ngurah; Sri Wahyuni, Ni Ketut (Jurnal Riset Kesehatan Nasional, 2020)
Diarrhea is the second leading cause of death in children in the world, as well as in Indonesia. To reduce mortality due to diarrhea, it needs fast and appropriate management. Probiotics have been widely used in cases of acute diarrhea in children but have not been recommended at the Klungkung Regional General Hospital. This study aims to determine the effectiveness of prebiotic administration on the duration of diarrhea in pre-school children.This type of quantitative observational research uses a comparative study design. This study involved 40 respondents who were selected based on inclusion and exclusion criteria with purposive sampling technique.The results showed that the duration of diarrhea in pre-school children given prebiotics averaged 23.74 or 24 hours 14 minutes, while the duration of diarrhea in pre-school children given standard therapy was on average 47 hours 49 minutes. The results of the Independent T Test obtained p value = 0.001 <0.05, which means that prebiotic administration is more effective than giving standard therapy to the duration of diarrhea in pre-treated children. Suggested to the Hospital so that prebiotics can be used as standard therapy for pediatric patients who suffer from diarrhea.Â Keywords: Prebiotics, Duration of Diarrhea, Pre-school ChildrenÂ